Modelling determinants of extinction across two Mesozoic hyperthermal events. Issue 1889 (24th October 2018) - Dunhill, Alexander M.; Foster, William J.; Azaele, Sandro; Sciberras, James; Twitchett, Richard J.
Abstract : The Late Triassic and Early Toarcian extinction events are both associated with greenhouse warming events triggered by massive volcanism. These Mesozoic hyperthermals were responsible for the mass extinction of marine organisms and resulted in significant ecological upheaval. It has, however, been suggested that these events merely involved intensification of background extinction rates rather than significant shifts in the macroevolutionary regime and extinction selectivity. Here, we apply a multivariate modelling approach to a vast global database of marine organisms to test whether extinction selectivity varied through the Late Triassic and Early Jurassic. We show that these hyperthermals do represent shifts in the macroevolutionary regime and record different extinction selectivity compared to background intervals of the Late Triassic and Early Jurassic. The Late Triassic mass extinction represents a more profound change in selectivity than the Early Toarcian extinction but both events show a common pattern of selecting against pelagic predators and benthic photosymbiotic and suspension-feeding organisms, suggesting that these groups of organisms may be particularly vulnerable during episodes of global warming. In particular, the Late Triassic extinction represents a macroevolutionary regime change that is characterized by (i) the change in extinction selectivity between Triassic background intervals and the extinction event itself; and (ii) the differences in extinction selectivity between the Late Triassic and Early Jurassic as a whole.